PERENCANAAN TEBAL LAPIS PERKERASAN LENTUR RUAS JALAN PENGHUBUNG DESA LAHA – DESA NEGERI LIMA - Paul, Rizky Steven; Betaubun, Renny James; Latar, Sjafrudin (Jurusan Teknik Sipil, 2024)
This research aims to plan the thickness of flexible pavement layers on road segments that have not been coated with pavement on the Laha-Negeri Lima road section, Central Maluku Regency. Through primary data collection, namely data obtained in the field including DCP, LHR survey, road dimensions, and documentation. While secondary data is data obtained from agencies, such as Ambon Island road maps, including field observations, interviews, and literature searches, and analysis using the 2017 Road Pavement Design Manual Method. This research determines the appropriate thickness of flexible pavement layers to facilitate inter-regional connectivity and increase local economic potential. The results of the analysis show that the thickness of the asphalt layer is adjusted to the Road Asphalt Plan Manual No.02/M/BM/2017 and the thickness of the flexible pavement layer on the Laha Village - Negeri Lima Village connecting road section along 3000 m is obtained AC WC 4 cm, AC BC 6 cm, AC BASE 7 m, and LFA Class A 30 cm. While the cumulative value of the standard load with a planning length of 3000 m and a width of 6 m is obtained in total 3,252,548 and an average CBR value of 8.17%.